Competition and density dependence in arid mountain forest stands: revealing the complex process from spatial patterns - Yang, Junlong; Yu, Jian; Wang, Guangping; Li, Xiaowei (Frontiers in Forests and Global Change, 2024)
Understanding the spatial patterns and interaction of trees is crucial for exploring forest dynamics. However, limited research has explored the spatial pattern and interactions between adult trees and their offspring population in arid mountain forest ecosystems. We investigated the spatial distribution and interaction of recruitment, survival, and mortality at different size classes in the Populus davidiana forest in the Luoshan Mountains (Ningxia, China), to gain insights into its stand dynamics. (1) This demonstrated the characteristic shift from an aggregated to random distribution as seedlings grew and developed into adult trees. (2) The adult trees exhibited strong positive and weak negative spatial associations with seedlings and saplings, respectively, with an increasing spatial scale, yet both stages underwent stark transitions from negative (1–15 m scales) to positive (> 20 m scale) associations. (3) Generally, the closer the individual trees were to each other, the greater the negative impact of neighboring trees on the size of an individual tree. (4) Additionally, adult trees strongly increased the risk of seedling mortality across the spatial scale of 0–50 m. (5) Live seedlings were less than the dead ones around dead seedlings. There was a stronger aggregation of dead seedlings than live seedlings. Moreover, the density-dependent mortality in our study rejected the random mortality hypothesis. In summary, these results suggest that spatial separation occurs between dead and live seedlings of P. davidiana. Under adult trees, negative dependence plays an important role in the arid mountain forest recruitment. Our findings will contribute to the restoration and conservation of arid mountain forests and provide theoretical support for forest management.